Assessment of Fasting Blood Glucose Level of Undergraduates in Abeokuta Ogun State Nigeria - , Nupo Sunday Sedodo; , Olunusi Patience Abosede; , O. A. Ilori; , M. K. Adenekan; , Ojo Mariam Idowu; , A. O. Nupo; , J. V. Akinlotan (Archives of Current Research International, 2020)
Objectives: Impaired Fasting Glucose (IFG) is a condition where Fasting Blood Glucose (FBG) is above normal but not high enough to be considered diabetic. Impaired fasting glucose is linked with many co-morbid diseases such as obesity, dyslipidemia and hypertension. The study assessed the prevalence of impaired fasting glucose concentration among undergraduates in Ogun state South-West Nigeria. Materials and Methods: A purposive sampling technique was used to select three hundred undergraduate students willing and ready participant. A pretested structured questionnaire was used to obtain the socio-economic information of the undergraduates. Fasting blood glucose, weight, height and blood pressure were determined using glucometer, weighing scale, height meter and sphygmomanometer respectively. Results: The result of the study showed that the prevalence of IFG among undergraduate in South West Nigeria was 11.0% (n=33) of total participants. A higher prevalence of impaired fasting glucose (IFG) was found with females than males. Body mass index of the subject reviewed that (11.0%, n=33) were underweight, (61.0%, n=183) had normal weight, (27.3%, n=82) were overweight and (0.7%, n=2) were obese. Conclusion: In conclusion, some of the participants had abnormal FBG (11%, n=33). Nutritional program/workshop should be organized by the institutions to enable undergraduates make a healthy, responsible lifestyle choices and consume a well-balanced diet.